Effects of Massage and Cold Water Immersion After an Exhaustive Run on Running Economy and Biomechanics: A Randomized Controlled Trial. Issue 1 (January 2022) - Duñabeitia, Iratxe; Arrieta, Haritz; Rodriguez-Larrad, Ana; Gil, Javier; Esain, Izaro; Gil, Susana M.; Irazusta, Jon; Bidaurrazaga-Letona, Iraia
Abstract : Abstract: Duñabeitia, I, Arrieta, H, Rodriguez-Larrad, A, Gil, J, Esain, I, Gil, SM, Irazusta, J, and Bidaurrazaga-Letona, I. Effects of massage and cold water immersion after an exhaustive run on running economy and biomechanics: A randomized controlled trial. J Strength Cond Res 36(1): 149–155, 2022—This study compares the effects of 2 common recovery interventions performed shortly after an exhausting interval running session on running economy (RE) and biomechanics. Forty-eight well-trained male runners performed an exhaustive interval running protocol and an incremental treadmill test 24 hours later at 3 speeds: 12, 14, and 16 km·h −1 . Subjects randomly received either massage, cold water immersion (CWI), or passive rest (control). Runners repeated the treadmill test 48 hours after the first test. A two-way mixed analysis of variance was performed comparing groups and testing times. The massage group had significantly better recovery than the control group at 14 km·h −1 in RE ( p < 0.05; η 2 = 0.176) and greater stride height and angle changes at 16 km·h −1 ( p < 0.05; η 2 = 0.166 and p < 0.05; η 2 = 0.208, respectively). No differences were observed between the CWI and control groups. The massage group had greater stride height and angle changes at 16 km·h −1 than the CWI group ( p < 0.05; η 2 = 0.139 and p < 0.05; η 2 = 0.168, respectively). Moreover, differences in magnitude suggested moderate effects on RE (η 2 = 0.076) and swing time (η 2 = 0.110). These results suggest that massage intervention promotes faster recovery of RE and running biomechanics than CWI or passive rest.